Single- and Multilevel Corpectomy and Vertebral body replacement for treatment of spinal infections. A retrospective single-center study of 100 cases - J. Neuhoff; O. Berkulian; A. Kramer; S. Thavarajasingam; A. Wengert; P. Schleicher; A. Pingel; F. Kandziora (Brain and Spine)
Background: The optimal operative approach for treating spinal infections remains a subject of debate. Corpectomy and Vertebral Body Replacement (VBR) have emerged as common modalities, yet data on their feasibility and complication profiles are limited. Methods: This retrospective single-center study examined 100 consecutive cases (2015–2022) that underwent VBR for spinal infection treatment. A comparison between Single-level-VBR and Multi-level-VBR was performed, evaluating patient profiles, revision rates, and outcomes. Results: Among 360 cases treated for spinal infections, 100 underwent VBR, located in all spinal regions. Average clinical and radiologic follow-up spanned 1.5 years. Single-level-VBR was performed in 60 cases, Two-level-VBR in 37, Three-level-VBR in 2, and Four-level-VBR in one case.Mean overall sagittal correction reached 10° (range 0–54°), varying by region. Revision surgery was required in 31 cases. Aseptic mechanical complications (8% pedicle screw loosening, 3% cage subsidence, 6% aseptic adjacent disc disease) were prominent reasons for revision. Longer posterior constructs (>4 levels) had significantly higher revision rates (p < 0.01). General complications (wound healing, hematoma) followed, along with infection relapse and adjacent disc infection (9%) and neurologic impairment (1%).Multilevel-VBR (≥2 levels) displayed no elevated cage subsidence rate compared to Single-level-VBR. Three deaths occurred (43–86 days post-op), all in the Multi-level-VBR group. Conclusion: This study, reporting the largest number of VBR cases for spinal infection treatment, affirmed VBR's effectiveness in sagittal imbalance correction. The overall survival was high, while reinfection rates matched other surgical studies. Anterior procedures have minimal implant related risks, but extended dorsal instrumentation elevates revision surgery likelihood.